(3aSGO PGJ GdHjf (B:s (3CSHGHg hGdJOGjHQ GdhGbjI efg (B/s - (3GdOYjL, YHO GdYRjR Hf MeO Hf OYjLs ((3ecI GdecQeI (B:s (3LGeYI Ce GdbQi (B:s (3cQSj eYGdj GdCSJGP GdOcJhQ eMeO YHOg jeGfj dEUdGM PGJ GdHjf,s, 2013)
(3jJfGhd cJGH (B((3aSGO PGJ GdHjf (B: (3CSHGHg hGdJOGjHQ GdhGbjI efg(B) (3hGdPj bGe HEYOGOg (B((3YHO GdYRjR Hf MeO GdOYjL(B) (3aj MhGdj (B(293) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCNdGb GdESdGejI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd HYfhGf CSHGH aSGO PGJ GdHjf, GdaUd GdKGfj HYfhGf GdJOGHjQ GdhGbjI ef aSGO PGJ GdHjf, GdMK Ydi eQYGI GdMbhb, GdEPf hGdJQNjU aj GdeOGQGQI hGdeYGQjV(B.s
(3HHdjhLQGajI (B: (3UaMI (B269-287.s
Keywords: (3GdCNdGb GdESdGejIs; (3GdhYX hGdEQTGOs